2021
DOI: 10.3389/fimmu.2021.650977
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Intrinsic CDK6 Is Dispensable for Anti-Viral and Anti-Tumor Responses In Vivo

Abstract: The cyclin-dependent kinase 6 (CDK6) regulates the transition through the G1-phase of the cell cycle, but also acts as a transcriptional regulator. As such CDK6 regulates cell survival or cytokine secretion together with STATs, AP-1 or NF-κB. In the hematopoietic system, CDK6 regulates T cell development and promotes leukemia and lymphoma. CDK4/6 kinase inhibitors are FDA approved for treatment of breast cancer patients and have been reported to enhance T cell-mediated anti-tumor immunity. The involvement of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
5
1
Order By: Relevance
“…This suggests that specific depletion of CDK6 in the TME triggers different mechanisms from dual CDK4/6 inhibition to regulate immune cell subpopulations and their activities to augment the anti-tumor response. While it has been reported that CDK6 depletion in T cells alone using the CD4-CRE system is not sufficient to suppress tumor growth, 50 our study showed that CDK6 depletion in all types of cells in the TME inhibited tumor growth via enhancing T cell activity and memory T cell differentiation. CDK6-depleted T cells may need priming from other types of CDK6-depleted immune cells to efficiently suppress tumor growth.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This suggests that specific depletion of CDK6 in the TME triggers different mechanisms from dual CDK4/6 inhibition to regulate immune cell subpopulations and their activities to augment the anti-tumor response. While it has been reported that CDK6 depletion in T cells alone using the CD4-CRE system is not sufficient to suppress tumor growth, 50 our study showed that CDK6 depletion in all types of cells in the TME inhibited tumor growth via enhancing T cell activity and memory T cell differentiation. CDK6-depleted T cells may need priming from other types of CDK6-depleted immune cells to efficiently suppress tumor growth.…”
Section: Discussioncontrasting
confidence: 67%
“…Intrinsic CDK6 deletion in T cells using the CD4-CRE system does not inhibit tumor growth. 50 Lack of costimulatory signaling may lead to immunological ignorance, as evidenced by several T cell receptor (TCR) transgenic models, while the anti-tumor effects are significantly enhanced when transgenic T cells are activated in vitro before cells are adoptively transferred into the host. 51 54 Thus, to determine whether CDK6 depletion in TCR-activated T cells enhances tumor suppression efficacy after adoptive transfer, we generated CDK6 KO OT-I mice by crossing OT-I transgenic mice with CDK6 KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were washed once before being equilibrated in a non-CO 2 incubator. A Mito Stress test was performed as previously described [ 73 ]. The drugs were used in the following final concentrations: oligomycin, 1.5 μM; carbonyl cyanide-p-trifluoromethoxyphenylhydrazone (FCCP), 2 μM; rotenone + antimycin A, 1 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of CD8 + T cells with CDK4/6 inhibitors enhances NFAT activity, increasing expression of CD25 and production of IL-2 and granzyme B, indicating that CDK6 may have a role in limiting T cell effector differentiation (Deng et al, 2018). Indeed, loss of CDK6 in T cells led to an increase in IL-2 production, and was also seen to impair type I interferon signalling events and increased metabolic processes resulting in enhanced ATP production and maximal respiration in addition to affecting proliferation (Klein et al, 2021).…”
Section: Cyclin-dependent Kinase Regulation Of T Cell Activationmentioning
confidence: 99%